2010
DOI: 10.1111/j.1538-7836.2010.04043.x
|View full text |Cite
|
Sign up to set email alerts
|

Platelet apoptosis by cold‐induced glycoprotein Ibα clustering

Abstract: To cite this article: van der Wal DE, Du VX, Lo KSL, Rasmussen JT, Verhoef S, Akkerman JWN. Platelet apoptosis by cold-induced glycoprotein Iba clustering. J Thromb Haemost 2010; 8: 2554-62.Summary. Background: Cold-storage of platelets followed by rewarming induces changes in Glycoprotein (GP) Iba-distribution indicative of receptor clustering and initiates thromboxane A 2 -formation. GPIba is associated with 14-3-3 proteins, which contribute to GPIba-signaling and in nucleated cells take part in apoptosis re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 44 publications
4
49
0
Order By: Relevance
“…2,21 Figure 1A confirms these observations for the ΔΨ m change and shows a 7-fold increase after incubation for 4 h at 0°C. Cold/rewarming initiates formation of TxA 2 .…”
Section: Changes In Mitochondrial Membrane Potential Induced By Arachsupporting
confidence: 76%
See 3 more Smart Citations
“…2,21 Figure 1A confirms these observations for the ΔΨ m change and shows a 7-fold increase after incubation for 4 h at 0°C. Cold/rewarming initiates formation of TxA 2 .…”
Section: Changes In Mitochondrial Membrane Potential Induced By Arachsupporting
confidence: 76%
“…We showed earlier that the ΔΨ m change in cold-stored platelets is accompanied by a fall in [14-3-3ζ-Bad]. 2 To investigate whether AA contributes to this process, platelets with blocked TPα were incubated at 0°C (4 h) and subsequently incubated at 37°C (1 h) and the complex was measured in immunoprecipitates of Bad. Cold/rewarming induced a fall in [14-3-3ζ-Bad] ( Figure 3A).…”
Section: Regulation Of the [14-3-3ζ-bad] Association By Arachidonic Acidmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4][5][6] Long-chain omega-3 fatty acids (LCn3-FAs) exert beneficial cardiovascular effects on atherosclerosis and inflammation and have been demonstrated to induce antithrombotic and antiplatelet effects and to reduce mortality. [7][8][9][10][11][12][13] Although the Alpha Omega Trial did not show a significantly different event rate among patients receiving LCn3-FA in addition to state-of-the-art therapy for myocardial infarction, 14 previous studies and subgroup analyses demonstrated a beneficial effect of omega (v)-3 FA.…”
Section: Introductionmentioning
confidence: 99%